1966
DOI: 10.1149/1.2423773
|View full text |Cite
|
Sign up to set email alerts
|

The Pressure Coefficient of the Hydrogen Electrode Reaction

Abstract: on active platinum electrodes is controlled by diffusion of molecular hydrogen. Results I obtained about 13 years ago ~A showed that the rate of the over-all reaction was unusually reproducible over a period of up to 16 days while the a-c impedance changed rather rapidly with time. Hence, it is probable that the over-all process does not depend on anything happening at the electrode surface. Similarly, the activation energy for the over-all process was about 5 kcal which is the order expected for a diffusion p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

1968
1968
2004
2004

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 19 publications
2
24
0
Order By: Relevance
“…However, Parsons 216) and Krishtalik 217) have proved that the activation volume obtained in Ref. 210 . Obviously, at potentials typical of ordinary cathodic reactions --far more positive compared to these values --it is unlikely that the processes occurring to a significant extent via the stage of formation of solvated electrons will take place in the above solvents.…”
Section: Possible Role Of Solvated Electrons In "Ordinary" Electrochementioning
confidence: 94%
“…However, Parsons 216) and Krishtalik 217) have proved that the activation volume obtained in Ref. 210 . Obviously, at potentials typical of ordinary cathodic reactions --far more positive compared to these values --it is unlikely that the processes occurring to a significant extent via the stage of formation of solvated electrons will take place in the above solvents.…”
Section: Possible Role Of Solvated Electrons In "Ordinary" Electrochementioning
confidence: 94%
“…The pressurizing fluid entering the electrochemical cell from the separator must be an electrical insulator and free from easily oxidizable or reducible impurities: hexanes [37], octanes, clean hydrocarbon white oil [1,2], heptane [38], or a mixture of isooctane and methylcyclohexane (10 : 90) [39] have given good performances and working pressures up to 10 kbar [39] are obtainable. These solvents are preferred to water or kerosene which were used in the past [40]. It can be foreseen that the upper limit of the pressures that can be reached by compressing a liquid in a piston-cylinder will be due to the freezing of the fluid or the possible rupture of the cylinders or piston.…”
Section: Pressure Generation By the Intrusion Of A Piston Into A Cylimentioning
confidence: 99%
“…It has been shown that contamination between the pressurizing fluid and the test solution can occur; however this can be prevented by using inert separators such as mercury, flexible diaphragms or bellows [40] or pistons [41]. Sealing of the pressure vessels is achieved by means of rubber O-rings supported when necessary by a steel-backing ring to prevent extrusion of the rubber between the body of the pressure vessel and the plug or cap.…”
Section: Pressure Generation By the Intrusion Of A Piston Into A Cylimentioning
confidence: 99%
See 1 more Smart Citation
“…Scaling was achieved by two ' 0 ' rings and dectrical contact made via a spot welded Fe wire. The solution (0.1 N NaOH prepared Srorn AiialaR reagent and doubly distilled water, pre-electrolysed and deoxygenated with 0,-free N,) was contained in parallel ground glass joints in each compartment, the outer sections G and H serving to transmit pressure to the solution in a manner similar to that employed by Hills and Kinnebrugh (1966). In order to avoid generation of oxygen, palladized Pd auxiliary electrodes were used, which were pre -charged with hydrogen before each run.…”
Section: Introductionmentioning
confidence: 99%